PENERAPAN MEDIA TRUTH OR DARE UNTUK MENINGKATKAN KEAKTIFAN SISWA DAN PEMAHAMAN FIKIH MATERI HAJI DAN UMRAH SISWA KELAS IX MTS SYEKH SUBAKIR NGLEGOK BLITAR - Arisiana, Thias; Zahroh, Nafifatu; 'Afuwah, Rifa (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
In the fiqh learning process in class IX MTs Sheikh Subakir Nglegok Blitar, obstacles were found in student engagement and understanding, especially regarding Hajj and Umrah material. Teacher-centered learning and the limited use of interactive media made students passive and less enthusiastic. This study aims to apply Truth or Dare media as an alternative for interactive and enjoyable learning. The research used the Classroom Action Research (PTK) method conducted in two cycles with class IX students of MTs Sheikh Subakir as subjects. Data were collected through observation, interviews, documentation, and comprehension tests. The results showed a significant increase in student activeness and understanding of Hajj and Umrah material after the implementation of Truth or Dare media. This media created a more dynamic learning atmosphere, increased student engagement, and supported students’ mastery of the content. In addition, the use of Truth or Dare fostered a collaborative learning environment, encouraged students to be more active in discussions, and increased their confidence in expressing ideas. These findings indicate that educational game media such as Truth or Dare are effective and worth considering as an innovative approach to improve students’ activeness and understanding in fiqh learning in madrasah settings.